THE THE EFFECT OF GIVING RICE HUSK CHARCOAL AND GANDASIL B FERTILIZER CONCENTRATION ON THE GROWTH AND YIELD OF PURPLE EGGPLANT (Solanum melongena L.): PENGARUH PEMBERIAN ARANG SEKAM DAN KONSENTRASI PUPUK GANDASIL B TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG UNGU (Solanum melongena L.) - Rohmad Indrajaya; Yonny Koentjoro; Felicitas Deru Dewanti (Universitas Wahid Hasyim, 2025)
Purple eggplant (Solanum melongena L.) is one of the horticultural commodities that is quite much in demand by the people of Indonesia. The need and demand for purple eggplant every year continues to increase along with the increase in population, but purple eggplant production in some areas is still quite low due to one of them is limited land due to land conversion and less fertile land. This research was conducted from December 2024 to March 2025 in Bulurejo Village, Rengel District, Tuban Regency, East Java. This research was designed using a completely randomised design (RAL) which was arranged factorially and consisted of two treatment factors. Factor The first factor is the provision of husk charcoal (A) which consists of four levels, namely A0: 0 g/plant (control), A1 100 g/plant (control), A2: 100 g/plant (control), A3: 150 g/plant (control): 150 g/plant, A2: 150 g/plant, A3: 200 g/plant. The second factor is the application of several concentrations of Gandasil B (G) consisting of four levels, namely: G0: 0 g/L (control), G1: 2 g/L, G2: 3 g/L, G3: 4 g/L. The results showed an interaction between the application of husk charcoal 200g/plant and the concentration of Gandasil B 3g/l (A3G2) which produced the highest number of total flowers per plant, total fruit per plant, and total fruit weight per plant but not significantly different from the treatment of a combination of the application of husk charcoal 150 g/plant (A2G2) and the concentration of Gandasil B 3 g/l and a combination of the aplication of husk charcoal 200 g/plant and the concentration of Gandasil B 4 g/l (A3G3).